Upper Lower Cambrian (upper Placentian-Branchian Series) of the Northern Antigonish Highlands, Nova Scotia: Faunas, and Revised Stratigraphy - E. Landing (Journal of Paleontology, 1995)
Lithostratigraphy and depositional and epeirogenic history of the upper Placentian Series (Cuslett-Fosters Point Formations of the Bonavista Group) and Branchian Series (Brigus Formation) are identical in the northern Antigonish Highlands; Cape Breton Island; and eastern Placentia Bay, southeastern Newfoundland. Preliminary evidence suggests that the lower Middle Cambrian is present in the field area. A unified, uppermost Precambrian–Lower Cambrian, formation- and member-level nomenclature is appropriate to Avalonian North America, and the stratigraphic nomenclature of southeastern Newfoundland is applied in northern mainland Nova Scotia. Latest Placentian shoaling and deposition of a peritidal carbonate lithosome and unconformable onlap of the trilobite-bearing Branchian Series occurred in shallow Avalonian shale basins from eastern Massachusetts to central England. Uppermost Placentian Series faunas are very diverse in the Fosters Point Formation. Limited similarities with the South Australian Lower Cambrian are indicated by the presence of Camenella sp. cf. C. reticulosa, Conotheca australiensis, and Hyptiotheca sp., but these forms do not contribute to highly resolved correlation. Twenty-eight taxa are illustrated from the upper Placentian and Branchian Series. Caveacus rectus n. gen. and sp., a phosphatic problematicum, is limited to the upper Placentian Series. The oldest, skeletalized, macrophagous predators are the Pseudoconodontida and the later appearing Protoconodontida (n. orders). The Pseudoconodontida includes the Protohertzinacea n. superfamily and Strictocorniculacea n. superfamily (with the Rhombocorniculidae and Strictocorniculidae n. families). Strictocorniculum vanallerum n. gen. and sp. is described. The tommotiid family Sunnaginiidae emend. includes Eccentrotheca, Sunnaginia, Kulparina, and Jayceia deltiformis n. gen. and sp.
Keywords: geology paleontology